Effects of Mn Substitution in YBa2Cu3O7-b Superconducting Ceramic - Ali Dihom, Mustafa Musa (2004)
The influence of manganese (Mn) substitution in copper (Cu), barium (Ba) and yttrium (Y) sites in the Y-Ba-Cu-O system namely: YBa2Cu3-xMnxO7-δ (0.00 ≥ x ≥ 0.5), YBa2-x MnxCu3O7-δ (0.00 ≥ x ≥ 0.5) and Y1-xMnx Ba2Cu3O7-δ (0.00 ≥ x ≥ 0.5) were studied. The samples were prepared using the conventional solid state sintering technique. The sintered temperature and soaking time were 920ºC and 24 hours respectively. The transport properties of the samples were measured using the four-point probe electrical resistance measurement and the magnetic properties were measured by using ac susceptibility. Scanning electron microscope (SEM) was used to identify the surface morphology while the phase of the samples was determined using x-ray diffraction (XRD) technique.